2009
DOI: 10.1016/j.jvs.2008.08.063
|View full text |Cite
|
Sign up to set email alerts
|

Plasma N-terminal pro-B-type natriuretic peptide as a predictor of perioperative and long-term outcome after vascular surgery

Abstract: NT-proBNP is an independent prognostic marker for postoperative cardiac events and long-term mortality in patients undergoing different types of vascular surgery and might be used for preoperative cardiac risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 21 publications
1
19
0
5
Order By: Relevance
“…(22) It has recently been shown that NT-proBNP is associated with adverse cardiovascular events and mortality in patients undergoing vascular surgery. (23) Another intriguing possibility is that higher HMWA in some patients might be indicative of a wasting process. (24) It has been shown that circulating adiponectin levels are higher in patients undergoing weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…(22) It has recently been shown that NT-proBNP is associated with adverse cardiovascular events and mortality in patients undergoing vascular surgery. (23) Another intriguing possibility is that higher HMWA in some patients might be indicative of a wasting process. (24) It has been shown that circulating adiponectin levels are higher in patients undergoing weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…8) Furthermore, some reports have stated that NTproBNP is useful as a prognostic indicator of cardiovascular events such as acute coronary syndrome, postoperative cardiovascular disease, and stable coronary artery disease. 11,12) Fukuda et al reported that a numerical formula based on blood BNP concentrations in chronic heart failure patients at discharge could predict prognosis after discharge with a high probability. 13) In other words, a high NTproBNP level may indicate heart failure requiring treatment and may also identify a poor outcome.…”
Section: Significance Of Ntprobnpmentioning
confidence: 99%
“…12 Studies also demonstrate that elevated preoperative BNP in patients undergoing aortic aneurysm repair, carotid endarterectomy, and peripheral vein bypass correlates with increased risk for postoperative cardiac events including nonfatal myocardial infarction and cardiovascular death. 13,14 However, the predictive value of BNP in PAD patients undergoing EVT remains unknown.…”
mentioning
confidence: 99%